Climate and The Amazon - Bunyard, Peter
when concerning ourselves with the future of the eart`s climate we must not make the grave mistake of couting only the quantities of carbon dioxide released into the atmosphere from the combustion of fossil fuels, while neglecting those from changes in vegetation cover.
Keywords: AMAZONAS - COLOMBIA - INVESTIGACIONES - PUBLICACIONES SERIADAS; AMAZONAS - COLOMBIA - CLIMA - PUBLICACIONES SERIADAS; AMAZONAS - COLOMBIA - CALENTAMIENTO GLOBAL - PUBLICACIONES SERIADAS